2022
DOI: 10.1108/jeas-07-2021-0138
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on financial structure and performance of Islamic banks: a comparative study with conventional banks in the GCC countries

Abstract: PurposeThe aim of this paper has twofold: (1) to explain and compare the financial evolution of Islamic and conventional banking sector in the Gulf Cooperative Council (GCC) countries before and during the COVID-19 pandemic and (2) to explore the key success factors that might affect Islamic and conventional banks performance before and mainly during COVID-19 pandemic period.Design/methodology/approachOrbis Bank Focus database and annual financial reports are used to collect financial information of Islamic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 39 publications
5
20
1
2
Order By: Relevance
“…Empirical studies assessing the risk and overall performance of IFIs have shown that these institutions have a high capacity of financial resistance during crises (Abdulle & Kassim, 2012;Rafiuddin & Alam, 2012;Mansor & Syed-Aun, 2017;Mihajat, 2021). They also revealed that IBs perform better than their conventional counterparts during periods of instability (Ftiti et al, 2013;El-Chaarani & Ragab, 2018;Almonifi et al, 2021). Mokhtar and Laldin (2009) argued that Islamic bankers can reduce the financial risk level because they work based on the 'assets market' principle whereas conventional banks operate based on the 'money market' principle.…”
Section: Literature Review Financial Resistance Of Islamic Financial ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies assessing the risk and overall performance of IFIs have shown that these institutions have a high capacity of financial resistance during crises (Abdulle & Kassim, 2012;Rafiuddin & Alam, 2012;Mansor & Syed-Aun, 2017;Mihajat, 2021). They also revealed that IBs perform better than their conventional counterparts during periods of instability (Ftiti et al, 2013;El-Chaarani & Ragab, 2018;Almonifi et al, 2021). Mokhtar and Laldin (2009) argued that Islamic bankers can reduce the financial risk level because they work based on the 'assets market' principle whereas conventional banks operate based on the 'money market' principle.…”
Section: Literature Review Financial Resistance Of Islamic Financial ...mentioning
confidence: 99%
“…Several studies have shown that Islamic financial institutions (IFIs) and IBs performed better than other banks during the global financial crisis of 2008(Beck et al, 2013Alqahtani et al, 2017;Nurfalah et al, 2018). El-Chaarani and Ragab (2018) also argued that IBs succeeded in controlling their liquidity risk and managing their profitability and financial structure during the Arab political crisis in several Middle East and North Africa (MENA) countries. For the authors, the conservative Islamic principles were the factors that led IBs to reduce the impact of uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies focused on COVID-19's impact on Islamic banks (Candera, 2020;Ichsan, Suparmin, Yusuf, Ismal, & Sitompul, 2021). Furthermore, studies by Almutairi (2022) and El-Chaarani, Ismail, El-Abiad, and El-Deeb (2022) compared the effect of COVID-19 on Islamic banks to that of conventional banks in Kuwait during the pandemic. Most of these prior studies only focused on the short-term effects of the pandemic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Since the beginning of the emergence of Islamic banking, the industry has continued to increase. Islamic banking operates based on the prohibition of interest and the profit and loss sharing system (El-Chaarani et al, 2022). Unlike the conventional interest-based banking system, Islamic banking operates its entire operation freely from the interest system.…”
Section: Introductionmentioning
confidence: 99%
“…Our World in Data has recorded a total number of Covid-19 cases in Indonesia has reached 6.11 million, and deaths due to this virus have been recorded at 157 thousand people. Undoubtedly, the Covid-19 Pandemic has impacted all aspects of life in developed and developing countries, including the banking sector and Islamic banking (El-Chaarani et al, 2022). Moreover, the Islamic banking system across the country suffers the COVID-19 shock (Le et al, 2022).…”
Section: Introductionmentioning
confidence: 99%